Challenges of Developing Speaking Skills of Undergraduate Tertiary Level Students in the Government Colleges in Bangladesh through Classroom Interaction and Their Possible Solutions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
purpose of this research is to identify barriers to English language learning that arise in the context of classroom discussion. This study looks at the challenges of using English as a medium of instruction and practice in Bangladeshi government universities. Data have been acquired utilizing research tools including questionnaires and interviews to identify the challenges. Based on a thorough review of qualitative and quantitative methods, recommendations have been made for students, educators, and authorities in Bangladesh to foster an atmosphere conducive to learning.But I expect that the lack of proper teaching-learning methods and a supportive environment, improper way of teachers' feedback, lack of desired knowledge to the students of tertiary level, lack of congenial environment, shyness nervousness among the students, lack of required level of vocabulary, lack of required grammatical knowledge, and unwillingness to use English in convectional settings are the obstacles to developing speaking skills through classroom interaction in Bangladesh.Some potential approaches to addressing the problems identified in this study have been proposed. For this, teacher training should be offered, students should be required to listen to English news and watch English movies, students should be motivated, and class sizes should be kept as small as possible.